Hatcheria macraei (Girard, 1855) (Siluriformes, Trichomycteridae): new record from northwestern Argentina - Fernandez, Luis Alfredo (2015)
The geographic distribution of Hatcheria macraei (Girard 1855), the Patagonian Catfish, is herein extended north of the Río Colorado headwaters, the previous northernmost record for the species. H. macraei is registered from the Río Jagüé, in the headwaters of the Río Desaguadero basin (Northwestern Argentina). Morphometric and meristic data of collected specimens are included.